Dietary Dose Conversion of Whole Grains and Non-soy Legumes between Mice and Humans - ZHI Li, ZHU Yiqing, ZHAO Liangxing, CHEN Rui, ZHAO Qingyu, WANG Chao, XUE Yong, SHEN Qun (Shipin Kexue)
Moderate intake of whole grains and non-soy legumes can improve glucose and lipid metabolism, but excessive intake may have an adverse effect. Due to the lack of corresponding conversion relationships, the intake of whole grains and non-soy legumes in mouse feed cannot directly serve as a reference for human intake. This paper introduces the addition levels of common whole grains and non-soy legumes in mouse feed and explores their relationship with the recommended dietary intakes (RDI) of common whole grains and non-soy legumes in humans using various methods, including equivalent coefficient, surface area ratio, body shape coefficient, food density, body surface area index, energy conversion, and nutrient conversion methods. The results indicate that the RDI of 50–150 g of whole grains and non-soy legumes in humans could be equivalently converted into addition of 5%–50% whole grains and beans in the feed of mice with a 3 g daily feed intake. Dietary addition of whole grains and non-soy legumes exceeding 50% might place mice at risk for overconsumption. This study provides an important reference for establishing the conversion relationship between the amounts of whole grains and non-soy legumes added to mouse feed and the RDI of whole grains and non-soy legumes in humans.